47.8k views
2 votes
I will show you the equation

User Whaleberg
by
4.4k points

1 Answer

3 votes

The given equations :

x + y = 1 (1)

5x + 3y = (-3) (2)

Multiply the equation (1) by 5

5(x + y) = 5 x 1

5x + 5y = 5 (3)

Subtract equation (3) and (2)

5x + 5y - (5x + 3y) = 5 - ( -3)

5x + 5y - 5x - 3y = 5 + 3

5x - 5x + 5y - 3y = 8

0 + 2y = 8

y = 4

Substitute the value of y = 4 in the equation (2)

5x + 3y = (-3)

5x + 3 (4) = (-3)

5x + 12 = (-3)

5x = -3 - 12

5x = -15

x = -15/5

x = (-3)

So, the solutions are : (x, y) = ( -3, 4)

Answer : (x, y) = ( -3, 4)

User Tejinder
by
4.3k points